An in-depth examination of the financial ratios of metals and mining companies in India - Rohit Bansal; Shivi Sinha; Manminder Kaur (Journal of Management and Science, 2025)
In the current global context, the metals and mining industry is regarded as one of the major areas of concern. The financial ratios of mining and metals companies in the Indian market are thoroughly examined in this paper. The study aims to shed light on these businesses' stability, performance, and financial health in an unstable economy. Drawing upon a dataset spanning multiple years, various financial ratios are scrutinized, including liquidity ratios, profitability indicators, leverage ratios, and efficiency measures. This paper analyses the comparative financial performance of Indian companies like Jindal Steel, Coal India, Hindalco Industries, Tata Steel, and Bharat Forge during 2020-2023. Various ratios have been used to evaluate the financial health of certain companies. These include the following: leverage, profitability, activity, liquidity, and market value. The result demonstrates that Coal India has the strongest current ratio, indicating strong short-term financial strength. From 2020 through 2023, Hindalco Industries generated more earnings per share of their shareholder’s investment than others. However, the profitability of Coal India was much better in 2020-23 comparto all other companies. Key findings reveal the sector's resilience in fluctuating commodity prices and regulatory changes. Moreover, the study identifies trends in financial performance across different segments of the metals and mining industry, shedding light on variations in profitability, efficiency, and risk management practices.